The Washington book : how to read politics and politicians - Lozada, Carlos (Simon & Schuster, 2024)
"The Washington Book is the perfect guide to the state of our politics, and then men and women who dominate the terrain. It explores the construction of personal identity, the delusions of leadership, and that mix of subservience and ambition that can define a life in politics. The more we read the stories of Washington, Lozada contends, the clearer our understanding of the competing visions of our country"--